Guide to introduced pest animals of Australia - West, Peter (CSIRO Publishing, 2018)
Australia's introduced vertebrate pest species cost at least $1 billion annually in economic, environmental, and social impacts. The Guide to Introduced Pest Animals of Australia is a comprehensive, practical guide to 60 introduced pest animal species present in Australia, including 27 mammals, 18 birds, nine freshwater fish, two amphibians, and four reptiles. It contains descriptive information to identify each species in the field, including distinctive physical characteristics, size, weight, colouration, diet, breeding behaviour, habitat preferences, and information about footprints, dung, scats, and audible animal calls. Each species profile is accompanied by practical management information, maps, and high-quality photographs -- allowing readers to learn about pest species in their local area, what problems they might cause, and what control options exist for management. This guide also contains a number of emerging high-risk pest species that may pose a significant threat to our natural environment, economy, agriculture, and human health. Whether you are a farmer, natural resource manager, public land manager, pest controller, teacher, student, field naturalist, or wildlife ecologist, this easy-to-use guide will help you identify Australia's most significant introduced pest animals in your local area.